Exposing Two Languages to A Young Child: Parent’s Strategies on A Child’s Language Development for Speech Delay - Almira Rizky Asmaria; Ni Luh Putu Sri Adnyani; Putu Suarcaya (Universitas Islam Negeri Palopo, 2025)
Raising bilingual children in this modern era is essential. The use of English is very important both in academic and future careers. Every parent needs to prepare for introducing English. This study examined how parent’s strategies successfully introduce two languages into their child and the effect of raising the child into bilingualism from birth. This study employed a couple of parents, members of families, professional therapies, who actively gave exposure to bilingual children. One Parent One Languages (OPOL) approach into this language policy, regular therapy for helping the languages disorder, and visual- non visual process learning languages are the strategies. This is a case study that was an analysis used by Creswell, which consisted of five stages. This study employs observation and some interviews as data collection methods. This study aims to give recommendations for parents, similar researchers, and future generations to raise any children into bilingualism as early as possible.